AYUSH System Providing Opportunities for Health Promotion and Wellness - Khyati; Dayal, Satya Manav (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Background: Ever since the world has been made humans have been living a healthy life of 100 years life expectancy. But as time passed lifestyles changed and people started practicing Apathya Ahara and Vihara ignoring the needs of their bodies just for the leisure of the materialistic world. Arogya means Complete Positive Health, which is the Fundamental Human Right. A known proverb says `Health is Wealth` which is true because a Healthy Mind and Body can only achieve the ultimate goal of life. Today when there are numerous diseases like COVID-19 are coming up there is a need to go back to our forgotten roots which is AYUSH. Materials and Methods: Various Ayurvedic Classical texts, articles, and journals have been analysed. Results: It has always focussed on Prevention and Healthy Living by individuals and communities. AYUSH can be the best way to reduce the burden of diseases from Country and World through its simple basic preventive Lifestyle Regimens to be followed by everyone in the World. That can be only through Health Promotion by AYUSH Practioners to the base level of Primary Health Care. Discussion: When everyone learns about the significance of AYUSH services then they will accept it by heart as they are the most affordable and accessible facilities. Presently it is the time to work collaboratively with the community, government, medical facilities and other sectors to achieve the Social Global Target of `Health for All`. Currently, the Concept of One Health is the main focus for all. Even though the government is trying its best to provide the best health care services, it is a shear responsibility of every individual to maintain his or her health by making good choices for achieving healthy longevity. Conclusion: The study concluded that encouraging AYUSH practices in the public and private sectors will lead to better health. An era of holistic health and integrated medicine has begun now and from here this will be proliferated to the world so that the social global target of one health can be achieved and all live a meaningful and balanced life.